PENERAPAN DISIPLIN TUTOR DI PKBM BINA KREASI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Septriana, Wahyuni; Jas, Jasfar; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is how to apply the discipline of teachers in the PKBM Bina Kreasi district of Tenayan Raya Kota Pekanbaru. The advantage of this research is to find out the application of the discipline by teachers to students / residents of learning. The purpose of this study was to find out how to apply the discipline of teachers in PKBM Bina Kreasi Pekanbaru City. This study uses a type of descriptive research with a qualitative approach, which aims to determine the application of discipline in the PKBM Bina Kreasi district of Tenayan Raya Kota Pekanbaru. The informants in this study were four people, namely teachers at PKBM Creative Development. Interviews are conducted on the basis of research indicators, namely the application of discipline consisting of all sub-indicators and consists of nine dimensions. The application of the tutor discipline to the PKBM Bina Kreasi district of Tenayan Raya Kota Pekanbaru can be seen on the basis of the results of interviews with teachers at PKBM via 18 questions. From the 18 questions it can be concluded that the application of discipline at PKBM Creation is flexible due to factors from the background of the learning community itself.Key Words: Application, Discipline, Tutor, In PKBM